Uji Aktivitas Ekstrak Etanol Daun Kersen (Muntingia Calabura) Terhadap Bakteri Staphylococcus Aureus Dari Luka Diabetes - Syahratul Hasanah; Meldawati; Razoki Lubis (STIKes Ibnu Sina Ajibarang, 2024)
Gangrenous wounds are wounds that occur due to diabetes complications caused by nerve damage and poor blood circulation which makes diabetic wounds unable to prevent infection. Infection is caused by the growth of microbes. High levels of sugar in the blood of DM sufferers provide food for microbes to reproduce. One of the bacteria that causes gangrene is Staphylococcus aureus. Plants that can be used as antibacterials are cherry leaves, also known as seri (Muntingia calabura L.), which contain tannins, terpenoids, saponins, flavonoids and polyphenols. This research aims to identify the antibacterial activity of cherry leaf extract against Staphylococcus aureus bacteria from DM wound wipes. This research was carried out in an experimental laboratory by applying the disc diffusion research method. The resistance is measured through the clear zone that extends around the paper disc. Kersen leaf extract was obtained through a maceration process with 96% ethanol solvent to obtain a thick extract of 0.074%. The test concentrations used were 12.5%, 25%, 50% and 75%. Positive control tetracycline 500 mg and negative control DMSO (dimethyl sulfoxide). The results of this research show that Kersen leaf extract inhibits the growth of Staphylococcus aureus bacteria in diabetic wounds. In concentrations of 12.5%, 25%, 50%, and 75%, the average diameter obtained was 2.70 mm, 4.67 mm, 6.30 mm, 7.89 mm. Conclusion: the effect of ethanol extract of cherry leaves on the growth of Staphylococcus aureus bacteria in diabetic wounds is antibacterial.